Poverty and development interventions that address behavioural risk factors of non-communicable diseases in low and lower middle income countries: a systematic review. (November 2016) - Pullar, Jessica; Allen, Luke; Townsend, Nick; Williams, Julianne; Foster, Charlie; Roberts, Nia; Mikkelsen, Bente; Wickramasinghe, Kremlin
Abstract: Background: Non-communicable diseases (NCDs) disproportionately affect low and lower middle income countries (LLMICs), where 80% of global NCD deaths occur. LLMICs are the primary focus of interventions to address development and poverty indicators. We aimed to synthesise the evidence of the impact of these interventions on the four primary behavioural risk factors for NCDs—unhealthy diets, physical inactivity, tobacco use, and alcohol use. Methods: Using a comprehensive search strategy we systematically searched four online databases (Medline, Embase, Web of Science, and Global Health) for primary research conducted in LLMICS, published between Jan 1, 1990, and Feb 15, 2016, with no language restriction. Studies involved development or poverty interventions that reported on outcomes relating to the four behavioural risk factors for NCDs. We extracted summary level data on study design, population, health outcomes, and potential confounders. The study is registered with PROSPERO, number CRD42016039030. Findings: From 2172 search results, 26 studies published between 1999 and 2015 met our inclusion criteria. Quality of included studies was poor and heterogeneity of outcome measures required narrative synthesis. Included studies were conducted in 24 LLMICs, with 12 from low-income African countries. One study measured physical activity, 26 measured dietary components, and none measured alcohol or tobacco use. Most papers (n=23) involved agricultural interventions. Primary outcome measures included micronutrient intake, child stunting, and dietary diversity with a focus on preventing undernutrition in women and children. Intensive agricultural interventions were associated with improved calorie, vitamin, fruit, and vegetable intake. However, the impact of interventions often relied on participants' land ownership or communicable disease status, or the study did not measure unhealthy food consumption. Only three studies measured adult obesity, two of which indicated that increased income and consequential food affordability had the potential to increase obesity. Interpretation: Although many interventions addressing poverty and development have potential to affect NCD behavioural risk factors, most fail to measure or report these outcomes. Existing evidence suggests a positive impact of agricultural-based food security programmes on the intake of nutrients, fruits, and vegetables. However, studies investigating the effect of improved income on obesity tend to show an increased risk. Embedding an assessment of the impact of NCDs into development programmes is crucial in the context of the UN Sustainable Development Goals and the rapid epidemiological transitions facing LLMICs. Funding: This project was commissioned byWHO (2015/577190-0 ). KW and NT are supported by a grant from theBritish Heart Foundation (006/P&C/CORE/2013/OXFSTATS ). The authors alone are responsible for the views expressed in this abstract and they do not necessarily represent the views, decisions, or policies of the institutions with which they are affiliated.